A simple method for the determination of acyclovir concentrations in human plasma using high-performance liquid chromatography - Asma Aboelezz; Maged Kharouba; Sherif Hanafy Mahmoud (SpringerOpen, 2024)
Abstract Background Acyclovir is an anti-viral medication given to treat herpes simplex and herpes zoster infection. In some severe conditions such as herpes encephalitis, acyclovir is administered intravenously. However, high acyclovir doses may cause acute kidney injury and low acyclovir dose may predispose the patient to inadequate exposure to acyclovir which could be fatal in some conditions. In such cases, the acyclovir plasma concentrations will potentially guide the diagnosis and management of the kidney injury. In this study, we provide a simple and time-efficient method for analyzing acyclovir in human plasma using high-performance liquid chromatography (HPLC). Results The process starts with a single protein precipitation step by adding acetonitrile to deproteinize 300 µL of plasma. The chromatographic separation conditions consist of a mobile phase of water: methanol (97:3, v/v), a flow rate of 1 mL/min, a run time of 17 min, and a detection wavelength of 254 nm. The calibration curve was linear over the range of (0.70-60 mg/L) (r 2 ˃ 0.99). The retention times of acyclovir and the internal standard were around 15 and 12 min, respectively. The intra-day and inter-day analysis of acyclovir in plasma using this method exhibited accuracy and precision of less than 7%, which lies within the acceptable range. Different greenness assessment tools confirmed that the proposed method is eco-friendly. Conclusion The proposed method of analysis of acyclovir in the plasma using HPLC is simple, green and accurate method. This method could be applied in clinical settings where monitoring acyclovir concentrations is essential as it has wide range of the concentrations that could be detected.